Infiltration of CD8+ cytotoxic T-cells and expression of PD-1 and PD-L1 in ovarian clear cell carcinoma - Mengdi Fu; Huimei Zhou; Jiaxin Yang; Dongyan Cao; Zhen Yuan (Scientific Reports)
Abstract Ovarian clear cell carcinoma (OCCC) is resistant to chemotherapy, with limited treatment options for advanced and recurrent disease. The prevalence of OCCC differs by region. Assessing the expression of programmed cell death ligand 1 (PD-L1), PD-1, and CD8+T cell infiltration in OCCC is crucial, as their correlation with patient survival may provide valuable prognostic insights. We collected data from 36 samples from 18 OCCC patients, including 18 pairs of tumors and adjacent nonneoplastic samples. The optimized multiplex immunofluorescence technique was used to stain paraffin sections for immune factors related to the immune microenvironment of OCCC and clinical prognosis. The expression of PDL1 and PD1 in the tumor cells and tumor stromal cells was not significantly correlated with prognosis. Professional quantitative pathological analysis software was used to count the CD8+ cytotoxic T-cells in tumor regions and adjacent nonneoplastic regions in postoperative specimens. There were more CD8+ cytotoxic T-cells in the adjacent nonneoplastic areas than in the tumor tissue samples (p < 0.001). Further analysis revealed that a difference in cell density between CD8+ non-tumor-infiltrating lymphocytes (NTILs) and CD8+ tumor-infiltrating lymphocytes (TILs) exceeding 70 cells/mm2 was associated with poorer progression-free survival (PFS) (p = 0.042). In adjacent nonneoplastic regions, worse PFS was significantly observed in patients with high CD8+ T-cell expression in both total and stromal cells than those with low expression (p = 0.012 vs p = 0.007). The presence of CD8+ T-cells had significant potential for predicting the prognosis of patients with OCCC, which lays a foundation for the development of biomarkers for immune checkpoint blockade treatment response in OCCC patients.